JEWels : teasing out the poetry in Jewish humor and storytelling - Zeitlin, Steven J.; Schram, Peninnah (Book collections on Project MUSE., 2023)
"JEWels is the first of its kind: the living tradition of Jewish stories and jokes transformed into poems, recording and reflecting Jewish experience from ancient times through the present day. In this novel hybrid--jokes and stories boiled down to their essence in short poems--Jewish witticism is preserved side by side with evocative storytelling and deepened with running commentary and questions for discussion. Illuminated here are jewels from journeys, from the Old Country, from Torah, shaped by the Holocaust, in glimpses of Jewish American lives, in Jewish foods, in conversations with God, and on the meaning of life. Jewish comedians (Lenny Bruce, Jackie Mason) appear alongside writers and musicians (Elie Wiesel, Sholem Aleichem, Itzhak Perlman) and Hasidic rabbis (the Baal Shem Tov, Rabbi Nachman of Breslov), yet most of the tellers are ordinary Jews. In this cacophony of ongoing dialogue, storytellers, rabbis, poets, and scholars chime in with interpretations, quips, and related stories and life experiences. In JEWels each of us can see our own reflection."--